2020
DOI: 10.1002/pbc.28751
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a structured exercise intervention after the completion of acute cancer treatment in adolescents and young adults

Abstract: Background: Cancer treatments are frequently associated with impaired physical fitness, quality of life (QOL), and fatigue, often persisting into survivorship. Studies in older adults with cancer have demonstrated benefits from exercise; however, this has not been rigorously investigated in adolescents and young adults (AYA). The aim of this study was to determine whether a structured 10-week exercise intervention was associated with improved cardiorespiratory fitness (VO 2peak), fatigue, and QOL in AYA who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 53 publications
2
26
1
Order By: Relevance
“…Recruitment rates in other non‐AYA exercise intervention studies of HCT survivors report enrollment rates ranging from 22% to 71%, with completion of follow‐up evaluations ranging from 58% to 79% 29–33 . In a recent AYA oncology exercise study in patients who completed cancer treatment (not including HCT), a recruitment rates of 68% was reported, which is similar to 65% reported in our study 34 …”
Section: Discussionsupporting
confidence: 85%
“…Recruitment rates in other non‐AYA exercise intervention studies of HCT survivors report enrollment rates ranging from 22% to 71%, with completion of follow‐up evaluations ranging from 58% to 79% 29–33 . In a recent AYA oncology exercise study in patients who completed cancer treatment (not including HCT), a recruitment rates of 68% was reported, which is similar to 65% reported in our study 34 …”
Section: Discussionsupporting
confidence: 85%
“…High-quality randomised controlled trials (RCTs) involving exercise during cancer therapy in AYA are lacking [ 13 ]. Limited research has demonstrated cardiorespiratory fitness (CRF) [ 14 ] and walk distance [ 15 ] benefits in AYA as a result of exercise following treatment. These studies report clear evidence of patient deconditioning including reduced CRF and strength, suggesting a need for earlier intervention to prevent such decline [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Limited research has demonstrated cardiorespiratory fitness (CRF) [ 14 ] and walk distance [ 15 ] benefits in AYA as a result of exercise following treatment. These studies report clear evidence of patient deconditioning including reduced CRF and strength, suggesting a need for earlier intervention to prevent such decline [ 14 , 15 ]. While not specific to AYA, research has reported a 5–26% decline in CRF during exposure to various chemotherapeutic regimens that may not recover following treatment [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is undeniable that greater cancer survival rate is a positive fact, but it also means that more people suffer severe adverse effects due to the treatment, which are even more severe in young patients [ 9 , 10 ]. However, these adverse effects do not occur exclusively during the disease, but also in cancer survivors as cardiotoxicity is one of the main morbidity causes due to chemotherapy treatments with anthracyclines and radiation [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these adverse effects do not occur exclusively during the disease, but also in cancer survivors as cardiotoxicity is one of the main morbidity causes due to chemotherapy treatments with anthracyclines and radiation [ 11 , 12 ]. Furthermore, the tendency to a sedentary lifestyle increases other risk factors such as risk of overweight or obesity, arterial hypertension, muscular atrophy, etc., which can drastically reduce the patient’s quality of life (QOL) [ 10 ]. Apart from other reasons, this is why the risk of early mortality is eight times higher in these patients compared to the general population [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%